Whole-genome analysis and antimicrobial resistance phenotype of Vagococcus fluvialis isolated from wild Niviventer - Zhou, Jian; Liu, Ying; Gu, Tao; Zhou, Jingzhu; Chen, Fengming; Hu, Yong; Li, Shijun (Frontiers in Microbiology, 2025)
Vagococcus fluvialis (V. fluvialis), a Gram-positive bacterium belonging to the Enterococcaceae family, has been associated with human infections, including bacteremia and endocarditis. Its zoonotic potential raises concerns for public health, yet research on its antimicrobial resistance and pathogenicity is still limited. This study aimed to isolate and characterize V. fluvialis from wild Niviventer, analyze its genomic features (including antimicrobial resistance and virulence genes), and evaluate its antibiotic susceptibility profile to assess potential public health risks. We first isolated V. fluvialis (strain 25C42) from the rectum of wild Niviventer, confirmed through Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) and 16S rRNA gene sequencing. Whole-genome sequencing (WGS) was performed using second-and third-generation technologies, with subsequent quality control and assembly. Six databases including KEGG, COG, CARD and VFDB were used for genome annotation. Antibiotic susceptibility was evaluated according to Clinical and Laboratory Standards Institute (CLSI) guidelines, determining the minimum inhibitory concentrations (MIC) for 16 antibiotics. Strain 25C42 was identified as V. fluvialis, confirmed by MALDI-TOF MS and 16S rRNA sequencing. WGS revealed a genome length of 2,720,341 bp, GC content of 32.57%. Functional genomic analysis identified 2,268 genes in the COG database and 2,023 genes in KEGG, highlighting key metabolic and cellular processes. Notably, 119 virulence genes and 65 antimicrobial resistance genes were found, indicating significant resistance potential. Phylogenetic analysis demonstrated a close relationship with other Vagococcus species, particularly V. fluvialis (ANI 98.57%, DDH 88.6%). Antibiotic susceptibility tests indicated strain 25C42 was resistant to clindamycin, tetracycline, rifampicin, cefoxitin and levofloxacin. Our findings reveal that the wild rodent-derived V. fluvialis strain 25C42 harbors clinically relevant antimicrobial resistance determinants and virulence-associated genes. The high genomic integrity and extensive functional gene annotation underscore its metabolic versatility. Notably, strain 25C42 exhibits significant antimicrobial resistance, necessitating ongoing surveillance and research to understand its implications for public health and environmental monitoring, as well as strategies for effective therapeutic intervention.